Formação inicial do curso de pedagogia da Universidade Estadual do Piauí (UESPI): ênfase nas percepções de discentes em relação à inclusão do público-alvo da Educação Especial - LAURINDO, Idecires dos Santos (2024)
This study deals with the theme of Perceptions of students of the Pedagogy Course at the State University of Piauí, in relation to the inclusion of the target audience of Special Education, in regular classes of Early Childhood Education and the initial years of Elementary School. With legal support, it was possible to take important steps in achieving the presence of children targeted by Special Education in regular education classes, however, access alone is not enough and for us to go beyond access, we consider it essential to train teachers able to develop anti- ability pedagogical practices. Thus, the question is: how has the initial training of students in the Pedagogy Course at the State University of Piauí been taking place in relation to the inclusion of the target audience of Special Education? The present study had the general objective of analyzing the initial training of the pedagogy course at the State University of Piauí in relation to the inclusion of the target audience of Special Education, according to the students' perceptions. An exploratory, descriptive research was developed, with a qualitative approach. The participants were six students from the ninth period of the full degree course in pedagogy at the aforementioned institution who carried out their teaching internship in regular Early Childhood Education classes and the initial years of Elementary Education with target children in Special Education. The data collection instruments were semi-structured interviews, which were analyzed using content analysis. The results indicate that the students' perceptions indicate unpreparedness to develop practices with the target audience of Special Education students and show a gap between the knowledge acquired throughout training and pedagogical practices from an inclusive perspective. The students' perceptions indicate that the training contributions acquired in the pedagogy course at the State University of Piauí were not able to contribute to minimizing the numerous exclusionary and/or integrationist barriers existing in the school environment, in pedagogical practices and, consequently, in our empowerment, of each day. Teacher training can be a powerful ally or a strong opponent to this process, contributing only to maintaining the existing reality. Analyzing this reality, we consider the need to seek theoretical-practical subsidies that enable transformations in the area of initial teacher training and the elimination of ableism in educational institutions.